Planktonic Tintinnid Community Structure Variations in Different Water Masses of the Arctic Basin - Chaofeng Wang; Xiaoyu Wang; Zhiqiang Xu; Qiang Hao; Yuan Zhao; Wuchang Zhang; Tian Xiao (Frontiers in Marine Science, 2022)
Information on tintinnid community structure variations in different water masses in the Arctic Basin is scarce. During the summer of 2020, tintinnid diversity and vertical distribution were investigated in the Arctic Ocean. A total of 21 tintinnid species were found in five water masses and each water mass had a unique tintinnid community structure. In the Pacific Summer Water (PSW), Salpingella sp.1 occupied the top abundance proportion (61.8%) and originated from the North Pacific. In the Remnant Winter Water (RWW), Acanthostomella norvegica occupied the top abundance proportion (85.9%) and decreased northward. In the Mixed Layer Water, Pacific Winter Water, and Atlantic-origin Water, Ptychocylis urnula had the highest abundance proportion (67.1, 54.9, and 52.2%, respectively). The high abundance distribution area of Salpingella sp.1 and A. norvegica were separated by the boundary of the Beaufort Gyre and Transpolar Drift. The above species could be indicator species of each water masses. The highest abundance proportion of Salpingella sp.1 contributes 81.9% to the dominance of 12–16 μm lorica oral diameter in the PSW, which indicated that the preferred food items of tintinnid were also getting smaller. The occurrence of North Pacific tintinnid in the PSW might be due to the increasing Pacific Inflow Water. Further studies are needed to explore the lasting period of this species and whether it can establish a local population under rapid Arctic warming progress.